Factors Associated with Management Outcome of Incomplete Abortion in Yirgalem General Hospital, Sidama Zone, Southern Ethiopia - Achamyelesh Gebretsadik (Hindawi Limited, 2018)
Background. Each year, several millions of women who underwent abortion also bear several consequences, including infection, massive blood loss, chronic pelvic pain, infertility, and death. Poor treatment outcomes also cause disability and death. The aim of this study was to determine factors associated with management outcomes of incomplete abortion in Yirgalem General Hospital. Methods. Health facility-based cross-sectional study design was used. Medical record review of 186 women who received abortion service from July 1st 2015 to June 30 2017 was done. Then the data were entered into the computer using epi info version 7.2 and exported into SPSS version 20, Descriptive analysis was done to determine social, demographic characteristics, and bivariate and multivariate logistic regression analysis were done to identify factors associated with management outcome of incomplete abortion, 95% CI and odds ratio used to present the result. Results. A total of 180 (96.7%) of cases managed for incomplete abortion was included in the study. Of this, 53.3% of patients with incomplete abortion belonged to age group of 18-25 years old. More than half incomplete abortion cases were managed surgically 122 (67.8%). Of the total, 36 (19.4%) of the patients developed unfavorable management outcome. Gestational age at which abortion occurs AOR = 3.39, 95% (1.29, 8.89) and delayed seeking of medical help AOR = 2.96, 95% (1.04, 8.4) were found to be significantly associated with unfavorable management outcome. Conclusion. High numbers of cases managed for abortion resulted unfavorable management outcome. However, no death occurred and major surgery done as the result of abortion management. Delayed seeking of medical care and seeking care past 1st trimester are significantly associated with unfavorable management outcomes. Therefore, awareness creation for adolescent and youth about prompt health-care seeking after the start of the first sign and symptom of spontaneous abortion should be strengthened.